Heating Experiments on Benthic Foraminifera Ammonia sp. to Assess the Suitability of Amino Acid-Based Dating - Hidayat, Rahmadi; Barianto, Didit Hadi; Surjono, Sugeng Sapto; Ali, Che Aziz (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Sub-milligram fossil biominerals, mainly benthic foraminifera, have been recently used to estimate the age of sediments determined from amino acid dating due to the minimum sample size requirement for reverse-phase high-performance liquid chromatography (RP-HPLC). This includes the collection of Ammonia sp., known as a key species occupying restricted lagoonal environments. However, an experiment has not been conducted to understand the racemization kinetics in order to examine the reliability of this species for amino acid racemization (AAR) geochronology. This research aims to determine the trend of the extent of racemization and the amino acid concentration, leading to the recommendation of Ammonia sp. shells as a dating specimen. The results exhibit a predictable pattern, demonstrating a consistently increasing extent of racemization after oven heating for up to 168 h without any indication of reversal pattern. The racemization rate differs from four selected amino acids reported in this study, where aspartic acid is the fastest, followed by glutamic acid, valine and isoleucine epimerization. Moreover, the consistent proportion of total amino acid and the decline of amino acid concentrations can be clearly observed following exponential decay. Therefore, this foraminifer can be used as an alternative specimen to establish amino acid-based geochronology, particularly in the depositional environment lacking other microfossils. Due to its confined habitat, amino acid-based dating of Ammonia sp. is considered applicable to understand the small environmental changes related to marginal marine successions.